Search Optimization of The Shortest Route Using the Generate And Test Algorithm - Padma Mike Putri M (IJISTECH (International Journal of Information System and Technology), 2022)
Searching is a search method that belongs to the science of Artificial intelligence. The Generate and Test algorithm is able to solve problems related to heuristic searches in the terminology of Artificial Intelligence. The problem that often occurs is the user's lack of understanding about the completion of the General and Test Algorithm so that it takes a lot of time and money to get the final value, for that we need a completion of the shortest path search to minimize costs and time. The General And test method is a method of solving search cases The shortest path using several points and weights of the journey where all points must be visited once and the end point of the journey is the same as the starting point of the journey. The final benefit of this research helps users to find a very good alternative to take a decision.